IMPLEMENTASI KEBIJAKAN PENDIDIKAN PESANTREN DI PONDOK PESANTREN NURUL UMMAH PUTRI KOTAGEDE YOGYAKARTA - Luthfiyana Nur Rohmah; Subiyantoro Subiyantoro (Tarbawy : Jurnal Pendidikan Islam, 2021)
Islamic education in Indonesia appeared at the same time as the entry of Islam in Indonesia. It only started with a group of members of the community then turned to mosques, and ended up in a pesantren educational institution. Pesantren which as an Islamic educational institution for the first time before the existence of formal education is always seen as one's eyes, and the lack of attention from the government. Pesantren education has always taught Islamic education, and in addition pesantren has also contributed a lot to education, especially Islamic education. The change of government also has a positive impact on the government's concern for pesantren. Pesantren education that is only limited to non-formal education is still considered lacking and there is discrimination in it. Various policy changes are always made until a special policy appears about pesantren, which triggers all activities in pesantren. The policy aims to improve the quality of pesantren education without having to change the characteristics and traditions in pesantren. Pondok Pesantern Nurul Ummah Putri as one of the boarding schools has not felt the change from the pesantren law that has been passed by the government. So that the need for equality in the policy.